Analysis of the surface roughness of 3D-printed occlusal splints fabricated using biocompatible resins - Sumit Gahletia; Ashish Kaushik; Ramesh Kumar Garg (BIORE Scientia Academy, 2024)
Nowadays, in order to promote innovation and sustainable product design and manufacturing of occlusal splints, the dental profession requires significant upgrades in the form of novel materials and cutting-edge manufacturing technologies. Researchers and Industry frontrunners are constantly challenged to improve the properties of splint developed using three dimensional scanning and resin printing to meet consumer demand, as the ability of dental practitioners to take accurate impressions remains a major obstacle in dental laboratories. The proposed study outlines a digital manufacturing process for occlusal splints created with three-dimensional scanning and resin printing. The study also analysed the occlusal splints in terms of geometrical preciseness and surface roughness along with the costs involved during 3D printing a resin-based occlusal splint. Occlusal splints were created by scanning impressions made on a typodont model and then designing them in 3D modelling software. The splints were developed in MIMICS and 3D printed to a thickness of 10 microns using Rigid white methacryalate based resin material on a 3D systems DLP Figure IV standalone resin 3D printer to create a biocompatible occlusal splint. Splint tooth height was determined for geometric analysis. Surface roughness of splintwas measured using SURFCOM surface roughness tester. Resins used in 3D printing were proven to produce geometrically precise splints, the study showed. In conclusion, UV curable resin-based occlusal splints that have been 3D printed and cured are recommended for patient usage due to their increased accuracy and the ability to save processing time.